Profil penggunaan kontrasepsi di klinik Nurjaya, Kabupaten Badung, Bali - Ida Bagus Arjuna; I Made Darmayasa (DiscoverSys Inc., 2022)
Background: Contraceptive services are a series of activities, including the provision of education, counseling, medical eligibility screening, provision of contraception, installation or revocation, and handling side effects or complications in an effort to prevent pregnancy. According to BKKBN, active birth control participants among Couples of Childbearing Age (CCA) in 2020 amounted to 67.6%. Bali is ranked 7th, with a participation rate of 66.9%. The pattern of choosing the type of contraceptive in 2020 showed that most acceptors chose to use injectable methods, followed by pills. There aren't many similar studies targeting private clinics. It is very interesting to conduct a study on the pattern of contraceptive use in Nurjaya Clinic, one of the private clinics in Bali that also organizes contraceptive programs. Methods: This study is a descriptive epidemiology survey. The sample in this study is secondary data in the form of a register of contraceptive acceptors in Nurjaya Clinic from November 2020 to October 2021. The instruments used in this study are patients' register data and data analysis techniques using univariate analysis that is calculated in percentages and presented in a table and narrated. Results: The use of injectable contraceptives is still the main choice of CCA in Nurjaya Clinic, with users at 78.5% of all contraceptive acceptors, followed by other methods, namely IUD at 13.9%, birth control pills at 6%, and implants at 1.6%. Injectable contraceptives were also the top choice in every age group, 92.6% in the 21year old age group, 74.2% in the 21 to 35-year-old age group, and 82.8% in the 35-year-old age group. Conclusion: The most widely used contraception use in Nurjaya Clinic is injectable contraceptives for all of the age groups of <21 years, 21-35 years, or >35 years. Latar Belakang: Pelayanan kontrasepsi adalah serangkaian kegiatan meliputi pemberian KIE, konseling, penapisan kelayakan medis, pemberian kontrasepsi, pemasangan atau pencabutan, dan penanganan efek samping atau komplikasi dalam upaya mencegah kehamilan. Menurut BKKBN, peserta KB aktif di antara Pasangan Usia Subur (PUS) tahun 2020 sebesar 67,6%. Bali menempati peringkat 7 dengan tingkat keikutsertaan KB sebesar 66,9%. Pola pemilihan jenis alat kontrasepsi pada tahun 2020 menunjukkan bahwa sebagian besar akseptor memilih menggunakan metode suntik, diikuti oleh pil. Masih sedikitnya penelitian serupa yang menargetkan klinik swasta, sangat menarik untuk dilakukan suatu penelitian mengenai gambaran penggunaan kontrasepsi di Klinik Nurjaya sebagai salah satu klinik swasta di Bali yang turut menyelenggarakan program KB. Metode: Penelitian merupakan survei epidemiologi deskriptif. Sampel dalam penelitian ini merupakan data sekunder berupa register akseptor KB di Klinik Nurjaya bulan November 2020 hingga Oktober 2021. Instrumen yang digunakan dalam penelitian ini adalah data register pasien serta teknik analisis data menggunakan analisis univariat yang dihitung persentasenya serta disajikan dalam bentuk tabel dan dinarasikan Hasil: Penggunaan kontrasepsi suntik masih menjadi pilihan utama PUS di Klinik Nurjaya, dengan pengguna sebesar 78,5% dari seluruh akseptor kontrasepsi, diikuti metode lainnya yaitu IUD 13,9%, pil KB 6%, dan implan 1,6%. Kontrasepsi suntik juga menjadi pilihan utama pada seluruh kelompok usia yaitu 92,6% pada kelompok usia 21 tahun, 74,2% pada kelompok usia 21-35 tahun, dan 82,8% pada kelompok usia 35 tahun. Kesimpulan: Penggunaan kontrasepsi paling banyak digunakan di FKTP swasta Klinik Nurjaya adalah KB suntik, baik pada kelompok usia <21 tahun, 21-35 tahun, maupun >35 tahun.